Detection and quantification of human metapneumovirus in pediatric specimens by real-time RT-PCR - Kuypers, Jane (J Clin Virol, 2005)
BACKGROUND: Human metapneumovirus (hMPV), a recently identified virus, causes respiratory illness in children. OBJECTIVES: A real-time reverse transcription-polymerase chain reaction (RT-PCR) assay was developed and used to detect and quantify hMPV in respiratory specimens. STUDY DESIGN: The quantitative RT-PCR assay amplified an approximately 70 base pair fragment from the hMPV fusion protein gene. The assay was validated and used to test respiratory specimens obtained from children seen at a hospital in Seattle, Washington, from December 2002 through May 2003. RESULTS: The assay detected 1000 hMPV copies/mL of specimen, did not detect 19 other respiratory viruses, and was able to detect and accurately quantify isolates from the four known hMPV genetic lineages in a proficiency panel of 20 previously tested samples. hMPV was detected in 52 (7.2%) of 719 pediatric respiratory specimens. The mean log 10 copies/mL of hMPV in the 52 positive specimens was 7.67 (range = 4.59–10.60). Children aged 7–12 months had a significantly higher hMPV prevalence (12.4%) than did children younger than 7 months (4.7%) (P < 0.005). Children in this age group also had significantly higher levels of hMPV in their respiratory specimens (mean log 8.43 copies/mL) than did the younger children (mean log 6.93 copies/mL) (P = 0.0025). CONCLUSIONS: The rapid real-time RT-PCR assay described here is a sensitive test for clarifying the epidemiology of and diseases associated with hMPV.